Migratory birdwatchers' dress code: an analysis of clothing color choices on bird responses and behavior - Yeza Sistia Haniva; Hamda Rofiqa; Mhd Yusuf Nasution; Khairiza Lubis; Widya Arwita (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the influence of observer clothing color on the responses and behavior of migratory birds during birdwatching activities. The method used was experimental field observation conducted in the Batubara Mangrove Park area, Historical Beach, by comparing two categories of clothing colors, namely bright colors and neutral colors. The research subjects focused on the migratory bird species Numenius madagascariensis, which is known to be sensitive to changes in the visual environment. Data were collected through direct observation of bird behavior, such as flight frequency, feeding activity, movement, and alertness level. The results showed that the use of bright clothing colors increased the birds' alertness response, characterized by increased frequency of movement and decreased foraging activity. Conversely, the use of neutral colors tended not to cause significant disturbance so that bird behavior remained natural. These findings confirm that clothing color selection is an important part of birdwatching ethics to minimize disturbance to animals and support research and conservation effectiveness.